2023
DOI: 10.1002/chem.202203719
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Yield of DNA Strand Breaks under Photoexcitation of a Molecular Ruby

Abstract: Photodynamic therapy (PDT) used for treating cancer relies on the generation of highly reactive oxygen species, for example, singlet oxygen 1 O 2 , by light-induced excitation of a photosensitizer (PS) in the presence of molecular oxygen, inducing DNA damage in close proximity of the PS. Although many precious metal complexes have been explored as PS for PDT and received clinical approval, only recently, the potential of photoactive complexes of nonnoble metals as PS has been discovered. Using the DNA origami … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 99 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, these lesions, namely DNA base oxidations, often require alkaline treatment to lead to a strand cleavage, so that the DNA damage remained mainly unnoticed in the employed assay. At the same time, it has been reported that 1 O 2 can also efficiently induce single-strand breaks directly [ 89 ], so that the observed low DNA cleavage under aerobic conditions may be assigned to such a reaction. Moreover, it should be noted that both 3 O 2 and 1 O 2 [ 46 ] might react with other intermediates formed during the photoreaction, for example by the reaction with C-radicals 4 and 5 to give peroxides such as 6 ( Scheme 4 ), by cycloaddition of 1 O 2 to alkene and diene units, or by deactivation of the excited state in a triplet-triplet annihilation [ 90 ], all of which leading to a reduced photocleavage efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, these lesions, namely DNA base oxidations, often require alkaline treatment to lead to a strand cleavage, so that the DNA damage remained mainly unnoticed in the employed assay. At the same time, it has been reported that 1 O 2 can also efficiently induce single-strand breaks directly [ 89 ], so that the observed low DNA cleavage under aerobic conditions may be assigned to such a reaction. Moreover, it should be noted that both 3 O 2 and 1 O 2 [ 46 ] might react with other intermediates formed during the photoreaction, for example by the reaction with C-radicals 4 and 5 to give peroxides such as 6 ( Scheme 4 ), by cycloaddition of 1 O 2 to alkene and diene units, or by deactivation of the excited state in a triplet-triplet annihilation [ 90 ], all of which leading to a reduced photocleavage efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, the DNA single and double strand breaks induced by irradiation of a molecular ruby have been quantified, which opens a new field of application for the Lab-on-a-DNA origami approach. 124 …”
Section: Discussionmentioning
confidence: 99%
“… 2023 29 e202203719 . 1 The [Cr(ddpd) 2 ] 3+ complex induces DNA strand breaks under UV/vis light, making it a potential photosensitizer for photodynamic therapy. By combining DNA origami technology with atomic force microscopy, the quantum yield of strand breaks was quantified to be between 1 and 4% .…”
Section: Key Referencesmentioning
confidence: 99%
“…Panel D shows (1) the molecular structure of the photosensitizer [Cr(ddpd) 2 ][BF 4 ] 3 and (2) quantum yields for strand breakage in ss- and ds-DNA sequences. Adapted with permission from ref ( 1 ). Copyright 2023 Wiley-VCH.…”
Section: Dna Damage Induced Upon Vuv Irradiation (30–220 Nm; 620–413 Ev)mentioning
confidence: 99%